AYURVED APPROACH TO PUTRAGHNI YONIVYAPADA W.S.R. TO HABITUAL ABORTION DUE TO TORCH INFECTION: CASE STUDY - Divya Pawar; Sameer Gholap (AYUSHDHARA, 2020)
Pregnancy is the start of an incredible journey that leads to great emotional fulfilment to woman. Pregnancy loss is a physically and emotionally demanding for couples. Recurrent Pregnancy Loss (RPL) is also called as Recurrent Miscarriage or Habitual Abortion. It is defined as three consecutive pregnancy losses prior to 20weeks of pregnancy from the last menstrual cycle (LMP). Putraghni is a condition where repeated pregnancy loss occurs because of Artava dosha, Rakta dosha, Ati raktasrava. The article is to understand the Putraghni Yonivyapada w.s.r. to habitual abortion caused due to TORCH Infection and to study the effect of Ayurvedic medicines in the management of Putraghni Yonivyapada w.s.r. to habitual abortion caused due to TORCH Infection. The method is the single arm, open labelled case study of the subject of 27 yrs age having repeated pregnancy loss who has been treated with Shamana Chikitsa throughout pregnancy, Matrabasti and Yonipichu in 8th and 9th months. Pregnancy continued with treatment. Antenatal visits and Ultrasonography observations gave positive outcomes with healthy foetal growth. Patient delivered a full term single live male baby vaginally on 27/10/2019 at 3:20PM with 2.8kg. No birth anomalies were detected. The selected treatment protocol i.e., Shamana Aushadha, Matrabasti and Yonipichu in 8th and 9th month are found very effective in the management of Putraghni Yonivyapada w.s.r. to habitual abortion caused due to TORCH Infection.